Tindak Pidana Penyebaran Aplikasi Malware Berbasis APK: Studi terhadap Fenomena Modus Lowongan Kerja dan Paket Palsu - Mhd. Raihan Rizqullah; Rahmat Surkhalid Nasution; Sabda Abdillah Lubis; Muhammad Ichsan Parinduri; Limrogate Immanuel (Pusat Riset dan Inovasi Nasional, 2025)
The development of digital technology has provided convenience in various aspects of life, but also presents new challenges in the form of cybercrime. One of the increasingly widespread modes in Indonesia is the spread of APK (Android Package Kit)-based malware via short messages offering fake job vacancies or fictitious package notifications. When the victim downloads and installs the application, the perpetrator gains access to personal data and banking accounts, which are then used for criminal acts. This phenomenon causes great financial and emotional losses for the community and tests the effectiveness of criminal law in dealing with technology-based cybercrime. This study uses a normative juridical approach with an analysis of laws and regulations, scientific literature, and actual case studies. The results of the study show that the perpetrators can be charged with Articles 30, 32, and 35 of the ITE Law, as well as provisions in the new Criminal Code. However, the implementation of law enforcement still faces challenges, such as digital evidence, limited investigator capacity, and minimal cross-country cooperation. Therefore, cyber law policy reform, increasing digital literacy in the community, and strengthening coordination between law enforcement agencies are needed.